Nilai-Nilai Toleransi dalam Film My Name is Khan Perspektif Pendidikan Multikultural - Mujrimin, Bayu; Faiki, La Ode; Ali, Dukhroini (Universitas Al Falah As Sunniyah Kencong Jember (UAS Press), 2025)
The film My Name is Khan (2010) presents a powerful narrative about a Muslim man's struggle against discrimination in post-9/11 America. This study aims to explore the values of tolerance and peace embedded in the film and their relevance to the context of multicultural education. Using a qualitative content analysis method and a hermeneutic approach, this research identifies several core values such as respect for diversity, rejection of violence, interfaith empathy, and a commitment to truth and justice. These values are strongly embodied in the character of Rizwan Khan, an autistic Muslim who conveys a message of peace and compassion to all of humanity. The findings reveal that My Name is Khan can serve as an effective educational medium to reinforce character building, tolerance, and multiculturalism among students. The study suggests that educators can utilize films as a tool to instill humanistic values in the learning process.